The Importance of Galician Thinking: a Multi-dimensional Hermeneutic Perspective - Coca, Juan R. (Madrygal. Revista de Estudios Gallegos, 2016)
Galician thinking has been very fruitful in the studies of intimacy and of the quotidian. A Galician thinker who gave much thought to these concepts was Carlos Baliñas. He proposed a hermeneutic theory that, in my judgement, can be understood as quotidian-conversational. This theory aims to study the origin of significance. Baliñas’s proposition has a social interest which is well rooted in a multi-dimensional hermeneutic perspective.